How Entrepreneurial University Model is changing the Indian COVID–19 Fight? - Samrat Ray; Dossou Yedehou Leandre (Путеводитель предпринимателя, 2021)
It is indeed a great misnomer to analyze the dimensions of academic capitalism with the steady rise of entrepreneurial university in lines with Western educational policies. It is indeed a long treaded journey in emerging underdeveloped economies which has given the notion of a dream of the next superpower wherein entrepreneurial universities are a very recent concept post liberalization of economy and change in governmental practices and loosing hold over bureaucratic affairs which has led more stronger the innovation landscape of industry–education–government nexus in building the nation. Recent years have seen the great crisis of COVID pandemic which has changed the ideologies and theoretical models underlying economic welfare states and the velocity of money running through society. Amidst huge literature in entrepreneurial university studies, very little work has been done which answers the very pertinent question and research gap of how the triple helix model arrived in India and how the central government in India changed its beliefs globally by inheriting such model in its innovation practices to champion the cause of bringing new products, economic welfare, product development; which transformed India’s idea of being an importer of healthcare facilities to an expert and exporter of medical facilities thus completely reversing the cycle of trade and global logistics in healthcare economic practices. This paper works on such exploratory case study concerning India’s success story in employing triple helix model of innovation in national policy practices and world economy.